Saints and Sanctity for Critical Times: the Hagiography of Caterina da Racconigi - Eleonora Cappuccilli (Acta ad Archaeologiam et Artium Historiam Pertinentia, 2024)
The hagiography of the prophet and Dominican tertiary Caterina da Racconigi (1476-1547) is an impressive testimony of the construction of sanctity in sixteenth-century Italy. The hagiographic narrative responds to the often-contrasting needs of the common people disappointed by the corrupt clergy and seeking a path to salvation; to the clergy that strove to revive popular devotion; and to some parts of the humanist circles, looking for an answer to the religious and intellectual doubt that especially originated after the Reformation. Through the analysis of some passages of the two extant hagiographies of Caterina da Racconigi – Vitta et legenda, written by Caterina’s confessors, and Compendio delle cose mirabili, written by the philosopher Gianfrancesco Pico della Mirandola – this article examinates the multi-layered meanings attributed to sanctity during the religious crisis of the sixteenth century. Reform, intellectual and religious doubt and certainty, and human freedom emerge as fundamental pillars of the hagiographic logic that shaped the language of sanctity.